2012
DOI: 10.1158/1078-0432.ccr-11-1135
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Gene Expression of IGF-1R Pathway Markers and Cetuximab Benefit in Metastatic Colorectal Cancer

Abstract: Purpose: This study examined potential correlations between markers related to the insulin-like growth factor-1 receptor (IGF-1R) pathway and clinical benefit from the anti-epidermal growth factor receptor (EGFR) monoclonal antibody cetuximab in metastatic colorectal cancer (mCRC).Experimental Design: Gene expression profiles for 70 pretreatment specimens from metastatic lesions of patients with chemorefractory mCRC receiving cetuximab monotherapy were analyzed using 74 predefined Gene-Chip probesets represent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Such a result could be explained by off-target, either or indirect, drug effects (38), affecting IGF1R (39), despite the absence of published data. In line with prior reports, Huang and colleagues showed that high IGF1R expression has prognostic value in patients with Kras wild-type colorectal cancers treated with cetuximab (40).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Such a result could be explained by off-target, either or indirect, drug effects (38), affecting IGF1R (39), despite the absence of published data. In line with prior reports, Huang and colleagues showed that high IGF1R expression has prognostic value in patients with Kras wild-type colorectal cancers treated with cetuximab (40).…”
Section: Discussionsupporting
confidence: 76%
“…In cells expressing high levels of RAF dimers, binding of vemurafenib to one member of RAF dimer transactivates non-drug-bound ATP-bound RAF, leading to ERK activation, cell proliferation, and cutaneous squamous cell carcinomas (45). Deleterious effects of EGFR inhibitor cetuximab were previously reported in colorectal studies as a result of KRAS mutations (40,(46)(47)(48)(49). Interestingly, Winder and colleagues showed that wild-type KRAS patients with germline polymorphisms in the IGF1 pathway treated with cetuximab had a significant increase in their risk for tumor progression (50).…”
Section: Discussionmentioning
confidence: 98%
“…Overexpression of IGF-1R has been reported in many human cancers [11][12][13][14][15]. In the literature it has been shown that this receptor plays an important role in cancer cell transformation, tumor cell survival and development [6,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IGF-1R activates the mitotic divisions and inhibit apoptosis of cancer cells through the activation of signaling MAP/ERK and PI3K/Akt-1 pathways [6,10]. Overexpression of IGF-1R has been observed in many cancers, including esophageal cancer [11], breast cancer [12], colorectal cancer [13,14] and lung cancer [15]. Due to the important contribution of this receptor to the process of carcinogenesis and metastasis, research on using IGF-1R as a therapeutic target in oncology is being conducted [16].…”
Section: Introductionmentioning
confidence: 99%
“…Both IR and IGF1R signaling pathways consist of two major branches, the PI3K-Akt pathway and the MAPK pathway. Any IR signaling activator also tends to activate oncogenic IGF1R signaling (Higashi et al 2010, Lewis et al 2010, Wu et al 2011, Huang et al 2012, Ma et al 2012. Few agents are known to selectively activate IR signaling without triggering IGF1R signaling.…”
Section: Introductionmentioning
confidence: 99%